On agile metrics for operations management: measuring and aligning agility with operational excellence - Carvalho, A. M. (2019)
High-quality performance in Operations Management has been measured through different Excellence frameworks, with special emphasis on Operational Excellence models. By allowing to track performance indicators, identify improvement opportunities, and tackle operational limitations, such frameworks have proven their validity throughout the years. However, and despite their history of success, these frameworks remain based on almost the same principles and criteria that were defined when they were first being established, more than three decades ago. As change becomes central to the life of organizations, the ability to reconfigure operations becomes vital for success. However, the current takes on Operational Excellence do not consider the ability to change in their assessments. In a marketplace in transformation, this is perceived as a limitation and draws criticism to Excellence frameworks. In the face of this gap, we develop, deploy and analyze the results obtained by an Organizational Agility assessment framework that is aligned with Excellence in Operations Management. This paper presents this process and highlights the main results of bringing Organizational Agility together with Operational Excellence in the measurement and pursuit of superior operational performance.